2016
DOI: 10.1016/j.ijgo.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Learning curves for laparoscopic hysterectomy after implementation of minimally invasive surgery

Abstract: Both TLH and LSH were readily adopted among a group of surgeons inexperienced in laparoscopy, although LSH might be easier to learn. Experienced surgeons have a steeper learning curve than do their inexperienced counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
3
17
0
2
Order By: Relevance
“…It has been proven that proficiency for single port access TLH was achieved after 40 cases which is definitely indicating towards a learning curve for the procedure after performing a certain number of cases. 15,20 The incidence of ureteral and bladder injuries is 0% to 2% and corresponds well to that in the current study. 23,24 There were no incidence of bowel and ureteric injury in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…It has been proven that proficiency for single port access TLH was achieved after 40 cases which is definitely indicating towards a learning curve for the procedure after performing a certain number of cases. 15,20 The incidence of ureteral and bladder injuries is 0% to 2% and corresponds well to that in the current study. 23,24 There were no incidence of bowel and ureteric injury in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is no standard case number agreed upon to reach a plateau in the learning curve for laparoscopic hysterectomy (Table III) under mentorship with a decrease of the mean duration of surgery from 136 min to 118 min. But additional procedures were included in TLH in some of their cases (14). However, Terzi et al reported a longer learning curve in their retrospective series with two inexperienced gynecologists, up to 75 cases with shortening of operating time from 76 minutes to 68 min (10).…”
Section: Discussionmentioning
confidence: 99%
“…(8,10,(12)(13)(14)(15).Rosen et al suggested as low as 16 cases in terms of duration of surgery for a trainee surgeon under supervision in a teaching hospital facility in which the operating time reduced from 180 minutes to 105 minutes (12). Twijnstra et al concluded that 25 cases suffice under a mentorship program to reach a plateau of the learning curve in a teaching hospital (15).…”
mentioning
confidence: 99%
“…A technikai kompetenciához szükséges beavatkozások száma 20-30 közöttire tehető. Ez az a műtéti szám, amelynek során a műtéti idő és a komplikációk számának progresszív csökkenése figyelhető meg [22]. Egy másik megfogalmazás szerint a tanulófázisnak addig kell tartania, amíg a műtétet végző orvos a műtéti technikát standardizált módszerrel el tudja végezni [21].…”
Section: Megbeszélésunclassified